Architects’ role in the shaping of innovative adaptable buildings in a sustainable built environment (2015)
The drive of every sociological study is to explore the changes that are taking place in society and what direction these transformations will take in the future. It must be noted that construction and technological issues demands a sociological explanation, hence the thrust of the study. The research is aimed at opening up new perspectives on the behaviour of architects and the workings of its social institutions. To discover general social pattern that emerges from individual or group actions and interactions of designers; which underpins new technological adoption. The research methods employed include examination of practised based case studies and interview in the adoption of innovative adaptable technologies in shaping a sustainable future for the built environment. Review of literatures carried out affirm the necessity for further investigations into the underlying socio-cultural dimensions at play in the formation of sustainable built environment in Sub Saharan Africa which include the prevailing local cultures. The paper conclude that adequate decision support mechanism and information is imperative to aid architects, designers, built environment practitioners and policy makers alike.